Analisis Produksi dalam Sistem Ekonomi Islam: Prinsip, Praktik, dan Implikasinya terhadap Kesejahteraan Umat - Choerunnisa, Alivia; Aisyul Hana, Ubaid; Sa’idatuurrohmah, Nur (Al-Musthofa: Journal of Sharia Economics, 2024)
This research aims to analyze production in the Islamic economic system with a focus on principles, practices and empowerment towards the welfare of the people. Islamic economics, which is based on sharia, offers a unique approach to production that is different from conventional economic systems. This study examines the basic principles of Islamic economics such as justice, balance and social responsibility, as well as how these principles are applied in production practices. Through a qualitative approach and literature analysis, this research finds that production in an Islamic economy does not only focus on material profits, but also considers moral and social aspects. The research results show that the application of Islamic economic principles in production can improve the welfare of the people through fairer distribution, reduce poverty, and create more ethical employment opportunities. In addition, this research identifies challenges faced in implementing the Islamic economic system, such as a lack of understanding and regulatory support. In conclusion, production in an Islamic economic system has great potential to improve the welfare of the people if implemented well, and further research is needed to overcome existing challenges and optimize the application of sharia principles in a modern economic context.